2012
DOI: 10.1017/s0967199412000251
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of Hoechst staining and UV irradiation on preimplantation development of parthenogenetically activated mouse oocytes

Abstract: Parthenogenetic activation of oocytes is a helpful tool to obtain blastocysts, of which the inner cell mass may be used for derivation of embryonic stem cells. In order to improve activation and embryonic development after parthenogenesis, we tried to use sperm injection and subsequent removal of the sperm head to mimic the natural Ca2+ increases by release of the oocyte activating factor. Visualization of the sperm could be accomplished by Hoechst staining and ultraviolet (UV) light irradiation. To exclude ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…Intriguingly, these experiments showed that the configuration of chromatin itself is not essential for full development of SN oocytes, but instead some unidentified material in the nucleus is required (INOUE et al 2008). This observation is consistent with earlier reports showing that unidentified non-chromosomal material present in the GVs and pronuclei is crucial for progression through both oocyte meiosis (POLANSKI et al 2005;HOFFMANN et al 2006) as well as through the earliest cell cycles of embryonic development (WAKAYAMA et al 2000;GREDA et al 2006;EGLI et al 2007). Indeed, INOUE and colleagues (2008) observed differences in the nucleolar organisation in the pronuclei of the zygotes obtained through fertilisation of NSN and SN oocytes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Intriguingly, these experiments showed that the configuration of chromatin itself is not essential for full development of SN oocytes, but instead some unidentified material in the nucleus is required (INOUE et al 2008). This observation is consistent with earlier reports showing that unidentified non-chromosomal material present in the GVs and pronuclei is crucial for progression through both oocyte meiosis (POLANSKI et al 2005;HOFFMANN et al 2006) as well as through the earliest cell cycles of embryonic development (WAKAYAMA et al 2000;GREDA et al 2006;EGLI et al 2007). Indeed, INOUE and colleagues (2008) observed differences in the nucleolar organisation in the pronuclei of the zygotes obtained through fertilisation of NSN and SN oocytes.…”
Section: Discussionsupporting
confidence: 92%
“…Prediction of the type of the oocyte chromatin could, therefore, allow selection of oocytes of high developmental potential for the ART or research purposes. Whereas live imaging of the prophase oocytes using Hoechst 33342 allows to reveal the type of chromatin conformation, the development of the oocytes selected in this way may be reasonably impaired due to the effect of dye and UV illumination (SMITH 1993;MASIDE et al 2011;GIL et al 2012;VERSIEREN et al 2014). Thus, especially for applications related to ART technologies, a non-invasive method is more appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultraviolet (UV) irradiation and excitable DNA‐specific dyes such as Hoechst 33342 (H342) have often been used to aid the visualization of the nuclear material and the polar body before enucleation (Estrada et al, 2008; Lee et al, 2008; Hickey et al, 2011) or to confirm the enucleation of recipient oocytes after manipulation (Kragh et al, 2005; Das et al, 2010; Koo et al, 2010; Biswas et al, 2011). Exposure of the recipient oocytes to H342 and UV irradiation, however, may be detrimental for oocyte developmental competence, as reported for several species including cattle (Smith, 1993; Dominko et al, 2000), goat (Velilla et al, 2002), rabbits (Yang et al, 1990), and mice (Versieren et al, 2010). We have recently demonstrated that the exposure of oocytes to H342 and UV irradiation has a deleterious effect on the development of in vitro‐fertilized porcine oocytes, with increasing exposure to UV irradiation (up to 30 sec) producing more drastic effects (Maside et al, 2011).…”
Section: Introductionmentioning
confidence: 82%
“…However, this repeated UV light exposure may cause intracellular damage (Erba et al, 1988) and cell apoptosis (Zhang et al, 1999;Zhang and Kiechle, 1998). Furthermore, nuclear staining by Hoechst may impair the developmental competence of embryos (Li et al, 2004;Maside et al, 2011;Versieren et al, 2012). The intriguing questions are why and how haES cells become into diploid spontaneously; which genes or signaling are involved in this conversion; and whether it is possible to maintain haploidy in vitro without using FACS.…”
Section: Challenges Of Haes Cellsmentioning
confidence: 99%